COMMUNITY- BASED APPROACH TO REDUCE EARTHQUAKE VULNERABILITY IN KATHMANDU VALLEY - Punya Sagar Marahatta (Faculty of Geography, Universitas Gadjah Mada, 2012)
Nepal is a vulnerable country in terms of multiple disasters and one of them is earthquakes.Disaster risk management experts believe that one of the ways to reduce thevulnerabilities is by adopting a community-based disaster risk management approach.Unfortunately, Nepal has limited resources; the culture of insurance against disastersdoes not currently exist. This paper describes the findings of research conducted intraditional settlements of Kathmandu Valley multiple case studies, household surveys,and community-based participatory research have identified that the culture ofparticipation in local development activities and fundraising at the local level couldcontribute to disaster risk management in traditional settlements of Kathmandu Valley. Thispaper thus suggests developing resilience governance at the community level throughconsumer cooperatives in order to reduce vulnerability to earthquakes and capitalize onalready existing financial, human, and social capital and resources.